#### Answer

-$\frac{1}{6}$

#### Work Step by Step

-$\frac{2}{3}$$\div$ 4=
=-$\frac{2}{3}$$\times$$\frac{1}{4}$=-$\frac{2\times1}{3\times4}$=
=-$\frac{2\times1}{3\times2\times2}$
=-$\frac{1}{6}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

-$\frac{1}{6}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.